Pengaruh CEO Narcissism dan Audit Quality terhadap Green Accounting pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2024 - Ribka Angely Yaputri Goni; Richard Friendly Simbolon; Mila Susanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyzes the influence of CEO narcissism and audit quality on green accounting in companies listed on the Indonesia Stock Exchange in 2024. The research method used is a quantitative approach with multiple linear regression analysis on 78 companies selected through purposive sampling technique. CEO narcissism variable is measured by the proportion of CEO photos displayed in the annual report, while audit quality is measured by the auditor's affiliation with the Big Four Public Accounting Firms. After conducting regression tests, it was found that CEO narcissism and audit quality have a negative and significant effect on green accounting, both partially and simultaneously. This indicates that the higher the CEO's narcissism and the stricter the audit quality, the lower the ESG score, indicating a reduced risk of environmental damage caused by the company. Overall, the combination of the two plays a significant role in determining the level of transparency and accountability of a company's sustainability reporting.